المكان المسرحي رؤیة فلسفیة - م.د.منى سلمان محمد (College of Education for Women, 2019)
The roots of the philosophical concept of place in the old human thought extended from his realization to the place he is being in, becomes the exsisting things that he noticed, form a space in the place. Since here the place is concedered as a container for these bodies. The initial (primitive) human being, through his concept of the place indicates the sensible phenomena of the concept of the place. Therefore, the concept of the sensible place, is the prevailing though during that period. Therefore, they distributed the world as (heaven, earth, and the sensible world) where (goods, human beings and the dead). The platonic concept to the idea of time is a circular concept depends on the absolute religious movement, because it is the movable image. So, the concept of place in the ancient human being's thought is prior to their concept of time and movement, because bodies cannot be found unless in a place determined by it's temporal moving nature. The Greek philosopher are the initial ones who discussed the concept of place according to the philosophical view of their age. This research includes four chapters: The first chapter is about the methodical fram which includes the problem of the research, its importance, goal and the definitions of terms. The second chapter includes the theoretical from and the previous studies. While the third chapter deals with the procedures of the research. Chapter four includes the results and the conclusion. The research ends with a list of sources and English abstract.